2020
DOI: 10.3390/su12093765
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Precision Agriculture Management Systems in Mediterranean Small Farms

Abstract: While the world population continues to grow, increasing the need to produce more and better-quality food, climate change, urban growth and unsustainable agricultural practices accelerate the loss of available arable land, compromising the sustainability of agricultural lands both in terms of productivity and environmental resilience, and causing serious problems for the production-consumption balance. This scenario highlights the urgent need for agricultural modernization as a crucial step to face forthcoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…PA applies traditional farming practices with new technology, practices, and economic drivers to enhance sustainability in a dynamic balance [15]. Studies have reported positive outcomes from PA adoption, including economic savings in productivity factors [16], increasing yield and environmental sustainability [17], and improving food security and community economic vitality in developing regions [18]. The International Society for Precision Agriculture (ISPA) provides clarity and guidance on this important concept, to achieve the agricultural production quality, create production profits, and improve the efficiency of resource use and environmental sustainability [19].…”
Section: Introductionmentioning
confidence: 99%
“…PA applies traditional farming practices with new technology, practices, and economic drivers to enhance sustainability in a dynamic balance [15]. Studies have reported positive outcomes from PA adoption, including economic savings in productivity factors [16], increasing yield and environmental sustainability [17], and improving food security and community economic vitality in developing regions [18]. The International Society for Precision Agriculture (ISPA) provides clarity and guidance on this important concept, to achieve the agricultural production quality, create production profits, and improve the efficiency of resource use and environmental sustainability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent technologies, such as the Internet of Things (IoT), make digital data acquisition and hence, smart farming possible [6]. In recent years, many studies have been performed in smart farming and precision agriculture [7][8][9][10][11][12][13]. Currently, Industry 4.0 acts as a transformative force on smart farming processes.…”
Section: Introductionmentioning
confidence: 99%
“…Precision farming utilizes information technology, sensor technologies, satellite technology, Artificial Intelligence (AI), and the Internet of Things for enhancing all functions and services of the agriculture sector (Khanal et al, 2017 andSchrijver et al, 2016). Moreover, precision farming implements techniques and technologies that highlight the relevance of integrating specific ecological principles and biodiversity management procedures into agrospace management, while optimizing inputs to maximize yields (Loures et al, 2020). For example, machine learning technology can be integrated with remote sensing for accurate forecasting of crop production and estimation of nitrogen levels in precision farming (Torky and Hassanein, 2020).…”
Section: Introductionmentioning
confidence: 99%